Terrestrial Laser Scanning for 3D Assets Registry - Suhari, Ketut Tomy; Purwanto, Hery; Sai, Silvester Sari (The Indonesian Journal of Computer Science, 2023)
This study aimed to assess the feasibility of using terrestrial laser scanning (TLS) technology for creating 3D asset registries in facilities management. The research utilized a case study approach to scanning an industrial facility, and the resulting data was processed to create a 3D model of the assets. The study found that TLS technology can produce highly accurate and detailed 3D models of assets, which can aid in asset management and maintenance. However, the technology has some limitations, such as cost and the need for skilled operators. The study suggests that TLS technology can be a valuable tool for asset management and recommends further research in this area.